Identification of Antecedents and Consequences of Professional Learning Community for Primary School Teachers - Amoozadeh, Raheleh; Shafizadeh, Hamid; Ahmadi, Fakhredin (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This research was conducted with the aim of identifying the antecedents and consequences of the professional learning community for primary school teachers. Method: In this article, a qualitative phenomenological method with stage analysis approach was used. The research participants consisted of 26 individuals, including university professors and faculty members in educational management, school principals, deputy principals, successful teachers in primary schools, and doctoral students or graduates in educational management working in education. They were selected through purposeful theoretical sampling. To collect data, in-depth interviews with research participants were utilized. For validity assessment, methods such as member checking, triangulation (three-point perspective) of data sources, peer review, and review by observers were used to enhance the validity of the research. Additionally, to examine reliability, strategies of dependability, credibility, confirmability, and transferability were employed. Findings: After data analysis, results showed that the antecedents of the professional learning community for teachers included four components: educational leadership, organizational culture, collaborative learning, and organizational structure. The consequences of the professional learning community for teachers consisted of three macro dimensions: development of performance quality, commitment to the job and school, and job and professional satisfaction. Conclusion: To realize the professional learning community for teachers, attention to the identified antecedents and consequences is necessary and essential. The duty of the professional learning community for teachers is to stimulate aspects such as mission, vision, collective commitment, and common goals, and to value creativity, risk-taking, initiative, and innovation, with the existence of an atmosphere based on mutual respect being an important part of the professional learning community for teachers.